(untitled) (Clinics, 2010)
OBJECTIVE: We aim to compare selective spinal anesthesia and general anesthesia with regard to postoperative recovery and fast-track eligibility in day surgeries. MATERIALS AND METHOD: Sixty geriatric outpatient cases, with ASA II-III physical status and requiring shortduration transurethral intervention, were enrolled in the study. The cases were split into 2 groups: as general anesthesia (Group GA) and selective spinal anesthesia (Group SSA). Group GA (n = 30) received propofol 2 mg kg-1 (until loss of eyelash reflex), remifentanil induction 0.5-1 µg kg-1, and laryngeal mask. Maintenance was achieved by 4-6% desflurane in 60% N2O and 40% O2 along with remifentanil infusion at 0.05 µg /kg-1 /min-1. Drugs were discontinued after the withdrawal of the ureteroscope, and extubation was carried out with 100% O2. Group SSA (n = 30) received 0.5% spinal anesthesia via L4-5 space by 0.5% hyperbaric bupivacaine 5 mg. Anesthesia preparation time, time to surgical anesthesia level, postoperative fast-tracking, and time to White-Song recovery score of 12, were noted. In the operating room, we evaluated hemodynamics, nausea/vomiting, surgeon and patient satisfaction with anesthesia, perioperative midazolam-fentanyl administration, postoperative pain, and discharge time. RESULTS: Anesthesia preparation time, length of surgery, anesthesia-related time in the operating room, time to sit, and time to walk were significantly low in Group GA (p < 0.05), whereas time to fast-track eligibility, length of stay in the PACU, discharge time, and other parameters were similar in both of the groups. CONCLUSION: While anesthesia preparation time, length of surgery, start time of surgery, time to sit, and time to walk were shorter in the General Anesthesia group, time to fast-track eligibility, phase 1 recovery time, and discharge time were similar among patients subjected to selective spinal anesthesia.